Effect of Surya-Namaskar on the Fitness Components and its Trends - Kaur, Rupinder; Chahal, Amit; Sharma, Sunil (International Research Journal of Ayurveda & Yoga, 2021)
Yoga plays a vital role as the ancient Indian healing art while dealing with the physical, mental, emotional, moral, and spiritual well-being. Yoga education is a process that helps in the all-around development of a human being. Suryanamaskar is a major part of yogic training that concentrates on physical health, mental health as well as spiritual health also. It is a sequential combination of 12 Yogic postures made up of a variety of spinal column forward and backward bending performed dynamically in synchrony with the breath. The objective of the study was to determine the effect of Suryanamaskar yogic training on the Components of Physical fitness i.e Strength, Speed, Endurance, Flexibility, and Coordination. The subjects for this study were selected from Punjab Engineering College (Deemed to be University), Chandigarh. A total of fifteen students were randomly selected for the study. Suryanamaskar was considered the independent variable and components of physical fitness were considered the dependent variable. Strength was measured by the handgrip dynamometer test in Kg. Speed was measured by the flying 30 meters test in time seconds. Endurance was measured by the sit-up test in 30 seconds. Flexibility was measured by the sit and reach test in cm. Coordination was measured by an alternate hand wall toss test. Repeated measure design was used for this study. The test was started four weeks prior to the treatment and thereafter every two weeks. Observations were taken up to the end of six weeks of training. To determine the effect of Suryanamaskar on fitness components, level of significance was set at 0.05 levels. In relation to fitness components, a significant (p< 0.05) effect of Suryanamaskar was found at the end of six weeks of training.